2020
DOI: 10.3389/fpls.2020.00369
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of OsMYB305 in Rice Enhances the Nitrogen Uptake Under Low-Nitrogen Condition

Abstract: Excessive nitrogen fertilizer application causes severe environmental degradation and drives up agricultural production costs. Thus, improving crop nitrogen use efficiency (NUE) is essential for the development of sustainable agriculture. Here, we characterized the roles of the MYB transcription factor OsMYB305 in nitrogen uptake and assimilation in rice. OsMYB305 encoded a transcriptional activator and its expression was induced by N deficiency in rice root. Under low-N condition, OsMYB305 overexpression sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 106 publications
0
19
0
Order By: Relevance
“…We identified 12 and 4 candidate genes related to root growth and nitrogen stress by integrating GWAS, WGCNA, and DEGs. For example, BnaA09g04260D, a major hub gene in the MEsalmon module and located in the region of the QTL cluster qcA09-1, encodes a major facilitator superfamily protein, whose homologous AtSTP13 had a potential role in root growth responses and nitrogen uptake under nitrogen-starved conditions [ 56 , 57 , 58 ]. Another hub gene in the MEsalmon module and the qcA09-1 region, BnaA09g05270D, has been reported to have a crucial role in regulating root gravitropism and elongation against various environmental stresses [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified 12 and 4 candidate genes related to root growth and nitrogen stress by integrating GWAS, WGCNA, and DEGs. For example, BnaA09g04260D, a major hub gene in the MEsalmon module and located in the region of the QTL cluster qcA09-1, encodes a major facilitator superfamily protein, whose homologous AtSTP13 had a potential role in root growth responses and nitrogen uptake under nitrogen-starved conditions [ 56 , 57 , 58 ]. Another hub gene in the MEsalmon module and the qcA09-1 region, BnaA09g05270D, has been reported to have a crucial role in regulating root gravitropism and elongation against various environmental stresses [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that overexpression of TaNAC2-5A TF significantly promoted the genes encoding NRT and GS under low N conditions in wheat [ 59 ]. Similarly, overexpression of OsMYB305 positively regulates OsNRT2.1 , OsNRT2.2 , and OsNiR2 expression, thereby promoting N uptake and assimilation in rice [ 60 ]. The expression levels of WRKY TF genes were upregulated in wheat under low-N conditions [ 22 ], WRKY proteins may contribute to the formation of complex signaling networks and thus improve plant tolerance to low-N stress [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…OsMYB305 encodes a transcriptional activator; its expression is enhanced in N deficient roots [100]. The overexpression of OsMYB305 enhances N uptake and assimilation, and improved growth under low N, increased tiller number, shoot dry weight, and total N concentration [100]. GROWTH-REGULATING FACTOR 4 (OsGRF4) is a transcriptional regulator of multiple N metabolism genes [101].…”
Section: N Signaling and Transcriptional Regulationmentioning
confidence: 99%